A grinding method of face gear mating with a conical spur involute pinion. (November 2019) - Zhou, Ruchuan; Zhao, Ning; Li, Wang; Li, Rui; Guo, Guodong; Guo, Hui
Highlights: A grinding method for the face gear mating with a conical spur involute shaper is proposed. The manufacture of four different examples of face gears is simulated. The deviations of the working surface of the ground face gear satisfy the prescribed precision. The deviations greater than the prescribed precision lie on the fillet surface and the root of the ground face gear. Abstract: A grinding method of face gear manufactured by a disk wheel is proposed in this paper. The computerized generation of the face gear by application of a conical spur involute shaper is presented. The tooth surfaces of the face gear are ground point by point with the disk wheel. In addition, a numerical model for determination of envelope residuals of the ground face gear surfaces is established. This model is used to determine the grinding tracks of the disk wheel according to the prescribed processing precision. The manufacture of four different cases of face gears is simulated by applying a simulation platform to illustrate the effectiveness of the proposed grinding method. The results show that deviations of excess greater than the prescribed processing precision only exist on the fillet surfaces and the root of the ground tooth, and increase from the fillet surfaces to the mean section of the root of the face gear. However, this has no influence on the meshing of the face gear drive. The processing efficiency of the face gear grinding is sufficiently affected by the prescribed processing precision.